Genetic Control of Fruit Yield and Its Component Characters in Hot Pepper {Capsicum Annuum L.) - Puozaa, D. (University of Ghana, 2010)
A research was conducted from June 2008 to May 2009 with the main objectives to identify suitable hot pepper lines to be used in breeding for superior fruit yield and yield associated components based on their combining abilities, determine heterosis in the Fi generation, estimate heritability of various traits and correlation between yield and its associated characters. Eight (8) hot pepper lines were analysed in a line x tester fashion comprising six (6) lines and two (2) testers. Analysis of variance of the mean performances of the Fis and their parents revealed significant differences among the genotypes implying the presence of variability. Parents and crosses showed significant differences in both general and specific combining abilities respectively indicating the incidence of both additive and non-additive gene effects. ‘BEK' was identified as the best combiner for fruit number/plant and earliness. The Fis expressed both positive and negative significant heterosis over better- and mid-parent values for all traits measured. Heritability was high for seed number, fruit length, number of primary branches, fruit weight, days to fruit set, days to first flower opening, fruit number per plant and plant height at flowering. It was low in fruit yield per plant Fruit number per plant was highly correlated with fruit yield per plant.
Thesis(MPhil)-University of Ghana, 2010